Nef does not inhibit F-actin remodelling and HIV-1 cell-cell transmission at the T lymphocyte virological synapse - Haller, Claudia; Tibroni, Nadine; Rudolph, Jochen M.; Grosse, Robert; Fackler, Oliver Till (European journal of cell biology, 2011)
Nef, a HIV-1 pathogenesis factor, elevates virus replication in vivo and thus progression to AIDS by incompletely defined mechanisms. As one of its biological properties, Nef enhances the infectivity of cell-free HIV-1 particles in single round infections, however it fails to provide a significant and amplifying growth advantage for HIV-1 on such virus producing cells. A major difference between HIV-1 cell-free single round infections and virus replication kinetics on T lymphocytes consists in the predominant role of cell-associated virus transmission rather than cell-free infection during multiple round virus replication. HIV-1 cell-to-cell transmission occurs across close cell contacts also referred to as virological synapse (VS) and involves polarization of the F-actin cytoskeleton, formation of F-actin rich membrane bridges as well as virus budding to cell-cell contacts. Since Nef potently interferes with triggered actin remodelling in several cell systems to reduce e.g. cell motility and signal transduction, we set out here to address whether Nef also affects organization and possibly function of the T lymphocyte VS. We find that in addition to increasing infectivity of cell-free virions, Nef can also moderately enhance single rounds of HIV-1 cell-cell transmission between Jurkat T lymphocytes. This occurs without affecting cell conjugation efficiencies or polarization of F-actin and HIV-1 p24Gag at the VS, identifying actin remodelling at the VS as an example of Nef-insensitive host cell actin rearrangements. However, Nef-mediated enhancement of single round cell-free infection or cell-to-cell transmission does not potentiate over multiple rounds of infection. These results suggest that Nef affects cell-free and cell-associated HIV-1 infection by the same mechanism acting on the intrinsic infectivity of HIV-1 particles. They further indicate that the high efficacy of cell-to-cell transmission can compensate such infectivity defects. Nef therefore selectively interferes with actin remodelling processes involved in antiviral host cell defense while actin driven processes that promote virus propagation remain unaltered.